Formalization of the process of freight car fleet management of operator company - Бутько, Тетяна Василівна; Шандер, Олег Едуардович (Eastern-European Journal of Enterprise Technologies, 2014)
The technology of freight car fleet management of operators company in the subsystems of UZ has been investigated and analyzed. It has been determined that the choice of the optimal plan of distribution of car operators according to the route of a freight car (schedule lines) mainly depends on the volume of cars being present at freight stations of railway network and their location in space and time. The topology variants of railway network has been analyzed using theory of graph taking into account all the above said. Relying on a systematic approach it has been proved, that the increase of railway transport competitiveness is possible at the expense of the provision of railway subsystem with invariance properties. The railway subsystem itself should be considered as a compromise between its stability and flexibility.Thus, optimization model which formalizes technological process of freight car fleet management of operator companies has been mode. The objective of the given model is presented in the form of total operating cost and relevant set of constraints that takes into account technological conditions of route formation. The mode optimization model adequately reflects the terms of transportation process, ensures the reduction of transportation costs under the condition of satisfaction of clients’ requirements and provides for the formation of automated technology of management of car fleet of different forms of ownership. Taking into account the theory of computational complexity, it is reasonable to choose heuristic method, based on mathematical apparatus of genetic algorithms, to obtain the optimal plan of car distribution according to the routes